Non-communicable disease mortality rates using the verbal autopsy in a cohort of middle aged and older populations in Beirut during wartime, 1983–93. Issue 4 (1st April 2001) - Sibai, A M; Fletcher, A; Hills, M; Campbell, O
Abstract : STUDY OBJECTIVES: Health priorities in middle to low income countries, such as Lebanon, have traditionally been assumed to follow those of a "typical" developing country, with a focus on the young and on communicable diseases. This study was carried out to quantify the magnitude of communicable and non-communicable disease mortality and to examine mortality pattern among middle aged and older populations in an urban setting in Lebanon. DESIGN AND PARTICIPANTS: A representative cohort of 1567 men and women (⩾50 years) who had participated in a cross sectional multi-dimensional health survey in Beirut, Lebanon in 1983 and were followed up 10 years later. Vital status was ascertained and causes of death were obtained through verbal autopsy. RESULTS: Total mortality rates were estimated at 33.7 and 25.2/1000 person years among men and women respectively. In both sexes, the leading causes of death were non-communicable, mainly circulatory diseases (60%) and cancer (15%). For all cause mortality, men had significantly higher risk than women (age adjusted rate ratio, RR=1.42, 95% confidence intervals (CI) = 1.16, 1.72) especially at younger ages. Except for cerebrovascular diseases, renal problems and injuries attributable to falls and fractures, men were also at higher cause specific mortality risk than women, in particular, for ischaemic heart disease (RR = 2.24, 95% CI = 1.62, 3.12). Comparison with earlier death certificate data in Lebanon and current estimates from other regions in the world showed the magnitude of cardiovascular disease over time. CONCLUSIONS: The results from this first cohort study in the Arab region show, in contrast with popular perception, a mortality pattern more like a developed country than a developing one. Strategies of public health activities, in particular for countries in transition, need to be continuously re-assessed in light of empirical epidemiological data and other health indicators for evidence-based decision making.